2011
DOI: 10.1111/j.1745-4514.2010.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Essential Oils of Different Parts of Laurel, Mountain Tea, Sage and Ajowan

Abstract: Oils obtained by hydrodistillation were analyzed by using gas chromatography (GC) and GC/mass spectrometry. 1, and a-terpinyl acetate (13.94% and 14.72%) were the main components from the essential oil of the stem and leaves of laurel, respectively. 1, and (E)-b-ocimene (24.88%) were the major compounds present in the essential oil of fruit. The main constituents of Salvia fruticosa oil were a-pinene (31.50%) and isoborneol (27.17%). b-pinene (20.53%), a-pinene (14.88%), cubebol (15.17%) and d-cadinene (12.99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The main components were 1,8-cineole (33.86-48.33%), ␣-terpinyl acetate (10.69-18.05%), methyl eugenol (2.98-12.48%), linalool (8.37-10.03%), ␣-pinene (5.33-10.87), sabinene (6.74-7.48%) and ␤-pinene (4.96-7.12%). When compared with earlier studies, the same volatile profile (1,8-cineole > ␣-terpinyl acetate > methyl eugenol) was also described for Italian (Flamini et al, 2007), Jordanian (Al-Kalaldeh et al, 2010) and Turkish specimens (Chalchat et al, 2011;Tabanca et al, 2013). In contrast it differed slightly from those originated from Brazil (da Silveira et al, 2014), Argentina (Lira et al, 2009) and Croatia (Politeo, 2009) where linalool was found as the second main compounds.…”
Section: Resultssupporting
confidence: 76%
“…The main components were 1,8-cineole (33.86-48.33%), ␣-terpinyl acetate (10.69-18.05%), methyl eugenol (2.98-12.48%), linalool (8.37-10.03%), ␣-pinene (5.33-10.87), sabinene (6.74-7.48%) and ␤-pinene (4.96-7.12%). When compared with earlier studies, the same volatile profile (1,8-cineole > ␣-terpinyl acetate > methyl eugenol) was also described for Italian (Flamini et al, 2007), Jordanian (Al-Kalaldeh et al, 2010) and Turkish specimens (Chalchat et al, 2011;Tabanca et al, 2013). In contrast it differed slightly from those originated from Brazil (da Silveira et al, 2014), Argentina (Lira et al, 2009) and Croatia (Politeo, 2009) where linalool was found as the second main compounds.…”
Section: Resultssupporting
confidence: 76%
“…These were the most abundant compound as well for our research. These compounds were reported in these articles as well: Derwich et al, sabinene (6.13%), α-pinene (3.72%) and β-pinene (3.14%) [12], Verdian-rizi, sabinene (5.8% -6.5%), α-pinene (2.6%-3.2%), β-pinene (2.4%-2.9%) [27], Chalchat et al, sabinene (7.07%), β-pinene (2.84%), α-pinene (3.17%) [28] and Moghtader and Salari, α-pinene (%5.25) and β-pinene (%3.99) [29] and also linalool is a bicyclic monoterpene, was found abundant in Bartin province (3.06%-3.83%). It has a significant effects against several symptoms especially in convulsions [30].…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Sesquiterpenoids: It was reported in 1971 [35] the isolation from laurel roots of the first sesquiterpene lactone: laurenobiolide (11). Since then, ten more lactones with a germacrane skeleton (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) have been isolated from roots [36,37], fruits [38,39] and leaves [37,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] (Figure 4). Dehydrocostus lactone (22), zaluzanin D (24) and eremanthin (26) were the first lactones isolated from laurel with a guaiane skeleton [38], and santamarine (28) and reynosin (31) the first ones with a eudesmane skeleton [40].…”
mentioning
confidence: 99%